Effect of Traditional Chinese Medicine enema combined with injection via gastric tube in the treatment of gastrointestinal dysfunction in ICU patients (中药胃肠联合治疗ICU患者胃肠功能障碍的效果观察) - ZHONG Yongjian (钟永建) (Association of Integrative Nursing, 2023)
Objective To observe the effect of Traditional Chinese Medicine Wenchang Tongfu decoction by enema combined with gastric tube administration on gastrointestinal dysfunction in ICU patients. Methods Totally70 critically ill patients with gastrointestinal dysfunction who were hospitalized in the Department of Critical Care Medicine from January 2022 to December 2022 were selected. They were randomly divided into the observation group and control group, with35 cases in each group. All patients received anti-infection, multiple organ support therapy, nasogastric tube placement and critical care nursing. The control group received Wenchang Tongfu decoction by gastric tube administration (50 mL every four hours, for 5 days), and the observation group received WenchangTongfu decoction by enema (150 mL every 6 hours, for 5 days)combined with gastric tube administration(50 mL every four hours, for 5 days). The general information, gastrointestinal function score, intra-abdominal pressure, and length of ICU stay of the two groups were analyzed. Results After 5 days of treatment, the gastrointestinal function score was decreased in both two groups, and gastrointestinal function score in the observation group was lower than that in the control group (P＜0. 01). The intra-abdominal pressure was decreased in both two groups, and intra-abdominal pressure in the observation group was lower than that in the control group (P＜0. 01). The ICU hospitalization time of the observation group was shorter than that in the control group (P＜0. 05). Conclusion The Wenchang Tongfu decoction by enema combined with gastric tube administration is effective to improve the gastrointestinal function and deduce the intra-abdominal pressure of ICU patients with gastrointestinal dysfunction, and shorten the length of ICU stays. (目的 观察中药温肠通腑汤胃肠联合治疗在ICU患者胃肠功能障碍患者中的应用效果。方法 选取2022年1月-2022年12月成都中医药大学附属医院重症医学科住院的危重症合并胃肠功能障碍患者70例, 采用随机数字表法分为观察组35例和对照组35例。两组均给予抗感染、器官支持、置入胃管等常规治疗及护理。观察组在此基础上给予温肠通腑汤每4 h经胃管注入50 mL, 每6 h经直肠滴入150 mL, 持续5 d; 对照组在此基础上予温肠通腑汤每4h经胃管注入50 mL, 持续5 d。分析两组一般资料、胃肠功能评分、腹内压、ICU住院时间。结果 治疗后, 两组患者胃肠功能评分均较治疗前下降, 且观察组胃肠功能评分低于对照组, 差异有统计学意义(P＜0. 01)。治疗后, 两组患者腹内压均较治疗前下降, 且观察组腹内压低于对照组, 差异有统计学意义(P＜0. 01)。观察组患者ICU住院时间较对照组缩短, 差异有统计学意义(P＜0. 05)。结论 温肠通腑汤胃肠联合治疗有效改善危重症合并胃肠功能障碍患者的胃肠功能, 降低腹内压, 缩短ICU住院时间。)